Vergnügen in der "Emporkömmlingsstadt". Soziale Scheidelinien in der populären Kultur Plauens im frühen 20. Jahrhundert. - Friedrich, Sönke (Deutsches Institut für Urbanistik, 2019)
Its growing textile industry tumed the town of Plauen in southwestem Saxony into a Großstadt (major city) at the tum of the 20th eentury. In the eontext of rapid demographie growth and urban development a great number of institutions of high and mass culture were established in plauen. This article explores the intereonneetions between urban social struetures and popular culture, referring to the diseourse on legitimate amusement in a 'city of arrivistes' (Emporkömmlingsstadt). Plauen's theatre, cinema, and musie hall were examples of a developing popular eulture, where neither social exclusion nor sophisticated cultural taste dominated. Thus, the eharaeteristics of the 'provincial' town of the 19th eentury were still important in a modemising city.
Keywords: Stadtgeschichte; Stadtgesellschaft; Vergnügungsstätte; Theater; Massenkultur; Tanzlokal